KESAHAN DAN KEBOLEHPERCAYAAN INSTRUMEN KOMPETENSI PENGAJAR TVET TERHADAP PENGAJARAN TEKNIKAL BERDASARKAN PENDEKATAN MODEL RASCH - Nur Yunus, Faizal Amin; Abdul Suki, Nabilah; Abd Baser, Jamil; Masran, Saiful Hadi; Marian, Mohd Fairuz; Rahim, Mohd Bekri (Online Journal for TVET Practitioners, 2017)
Pilot study carried out to verify and check on reliability instrument for TVET instructor competency. Instrument consists of 60 items and distributed to 30 of TVET instructor that involved with technical education at Institut Latihan Perindustrian Pasir Gudang, Johore. Instrument are developed to measured three (3) construct; i) technical aspect ii) learning and methodology aspect and iii) humanity and social aspect. Through this approach, respondent and item reliability been measured with more accurate than using Alpha Cronbachs’ value. Rasch Measurement Model (using Winstep version 3.69. 1. 11) measured the reliability and separation item- respondent, Point Measure Correlation (PTMEA CORR), fitness of item to measure the construct (outfit Mean-Square or MNSQ) and Standardized residual Correlation. This approach allows expelled of item that not follow the requirement based on the diagnosis. Final result of analysis, out of 60 item, 7 item need to be expelled and the rest of the item, which is 53 item are suitable to measure three (3) construct TVET instructor competency towards technical lesson. Respondent consist of real respondent as this study only involved pilot study.